Do I Really Know You? Do You Really Know Me? And, How Important Is It that We Do? Relationship and Empathy in Differing Learning Contexts - Elizabeth Kasl; Lyle Yorks (Adult Education Research Conference, 2014)
Pedagogical strategies that promote empathy foster learning by supporting meaningful dialogue. Aware that these strategies create risks as well as benefits, educators can make judgments about their potential value by examining relational power, positionality and emotional valence.